Designing evidence-based support aids for social media access for individuals with moderate-severe traumatic brain injury: A preliminary acceptability study - Fangyun Zhao; Fangyun Zhao; Hajin Lim; Emily L. Morrow; Lyn S. Turkstra; Melissa C. Duff; Bilge Mutlu (Frontiers Media S.A., 2022)
BackgroundAdults with traumatic brain injury (TBI) report significant barriers to using current social media platforms, including cognitive overload and challenges in interpreting social cues. Rehabilitation providers may be tasked with helping to address these barriers.ObjectivesTo develop technological supports to increase social media accessibility for people with TBI-related cognitive impairments and to obtain preliminary data on the perceived acceptability, ease of use, and utility of proposed technology aids.MethodsWe identified four major barriers to social media use among individuals with TBI: sensory overload, memory impairments, misreading of social cues, and a lack of confidence to actively engage on social media platforms. We describe the process of developing prototypes of support aids aimed at reducing these specific social media barriers. We created mock-ups of these prototypes and asked 46 community-dwelling adults with TBI (24 females) to rate the proposed aids in terms of their acceptability, ease of use, and utility.ResultsAcross all aids, nearly one-third of respondents agreed they would use the proposed aids frequently, and the majority of respondents rated the proposed aids as easy to use. Respondents indicated that they would be more likely to use the memory and post-writing aids than the attention and social cue interpretation aids.ConclusionsFindings provide initial support for social-media-specific technology aids to support social media access and social participation for adults with TBI. Results from this study have design implications for future development of evidence-based social media support aids. Future work should develop and deploy such aids and investigate user experience.